Cecum axis (CecAx) preservation reveals physiological and pathological gradients in mouse gastrointestinal epithelium - Hannah M. Lunnemann; Nicolas G. Shealy; Michelle L. Reyzer; John A. Shupe; Emily H. Green; Uswah Siddiqi; D. Borden Lacy; Mariana X. Byndloss; Nicholas O. Markham (Gut Microbes, 2023)
ABSTRACTThe mouse cecum has emerged as a model system for studying microbe-host interactions, immunoregulatory functions of the microbiome, and metabolic contributions of gut bacteria. Too often, the cecum is falsely considered as a uniform organ with an evenly distributed epithelium. We developed the cecum axis (CecAx) preservation method to show gradients in epithelial tissue architecture and cell types along the cecal ampulla-apex and mesentery-antimesentery axes. We used imaging mass spectrometry of metabolites and lipids to suggest functional differences along these axes. Using a model of Clostridioides difficile infection, we show how edema and inflammation are unequally concentrated along the mesenteric border. Finally, we show the similarly increased edema at the mesenteric border in two models of Salmonella enterica serovar Typhimurium infection as well as enrichment of goblet cells along the antimesenteric border. Our approach facilitates mouse cecum modeling with detailed attention to inherent structural and functional differences within this dynamic organ.